Peran Mahasiswa KKN Dalam Menanggulangi Perilaku Bullying di SDN 13 SALAK - Indra Yeni; Tiara Amelia; Wahyudi Pratama; Nurul Husna Khairani; Mutiara Hamidah (CV. ITTC INDONESIA, 2025)
The research conducted by the Community Service Program (KKN) students of Padang State University in Salak Village, Talawi District, Sawahlunto City aims to evaluate the role of KKN students in overcoming bullying behavior at SDN 13 Salak through socialization activities. The method used is descriptive qualitative with a participatory approach, where data is collected through observation, focus group discussions (FGD), and documentation. The subjects of the study were students in grades 5 and 6 who were actively involved in socialization activities. The results of the study showed an increase in students’ understanding of bullying, changes in attitudes towards bullying, and active participation in discussions and case reporting. Based on the theories of Bandura, Vygotsky, Ajzen, and Bronfenbrenner, the activities that have been carried out have proven effective in forming social awareness and positive attitudes of students towards preventing bullying in elementary school environments..